Contention Between English as a Second Language and Special Education Services for Emergent Bilinguals with Disabilities - Solange A. Lopes-Murphy (Universidad de La Sabana, 2020)
Tensión entre el inglés como segunda lengua y los servicios de educación especial para bilingües emergentes con discapacidades Tensão entre o inglês como segunda língua e os serviços de educação especial para bilíngues emergentes com deficiências The debate surrounding the prioritization of services for emergent bilinguals with disabilities is an area in need of attention. The generalized belief that disability-related services must take priority over English as a Second Language services suggests that there is a critical need to develop school professionals' understanding that these learners, in addition to receiving special education services, need substantial support in developing their second language abilities. The steady growth of emergent bilinguals and multilinguals in public schools, that is, students acquiring English as a new language, calls for well-trained practitioners able to meet these students' diverse linguistic, academic, cultural, emotional, and intellectual needs. The typical challenges this population faces acquiring a new language have, well too often, been misrepresented, neglected, or led them to programs for students with true disabilities. However, when emergent bilinguals are legitimately referred to special education, it is not uncommon for their disability-related needs to be prioritized over their English as a Second Language-related needs, and they end up not receiving the support they need to develop social and academic skills in the new language. This review article is intended to stimulate reflection on the types of services being delivered to emergent bilinguals and multilinguals with disabilities in U.S. public school settings. To reference this article (APA) / Para citar este artículo (APA) / Para citar este artigo (APA) Lopes-Murphy, S. A. (2020). Contention between English as a second language and special education services for emergent bilinguals with disabilities. Latin American Journal of Content & Language Integrated Learning, 13(1), 43-56. https://doi.org/10.5294/laclil.2020.13.1.3 Received: 29/09/2019 Accepted: 18/02/2020 Published: 28/08/2020